Indian Priest, Trinidad - (:unkn) unknown (My University, 2008)
Photograph of an East Indian holy man in traditional wear, reading a sacred text.
Colour: Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; Hindu priests--Trinidad and Tobago; East Indians--Trinidad and Tobago; Turbans--India; Necklaces--India; Ethnic costume--India; Men--Trinidad and Tobago; Trinidad and Tobago